Covıd-19 Pandemisinin Ekonomik, Toplumsal Ve Siyasal Etkileri 2020
DOI: 10.26650/b/ss46.2020.005.11
|View full text |Cite
|
Sign up to set email alerts
|

Covıd-19 Salgın Sürecinde Kadın ve Hane İçi Emeği

Abstract: Bu çalışmada COVID-19 salgın sürecinde kadınların hane içindeki ücretsiz emeği ele alınmıştır.Çalışmanın amacı, süresi ve sürecinin gelişimi belli olmayan 21. yüzyılın salgın koşullarında kadınların hane içinde sundukları ücretsiz emekleri üzerindeki değişimin anlık olarak fotoğrafını çekmek ve durum tespiti yapmaktır. Çalışan kadınlar için ikinci vardiya olarak değerlendirilen hane içindeki ücretsiz emek sürecinin salgın ile birlikte, evden çalışmaya başlayan kadınlar için tek ve bütüncül bir vardiyaya dönüşt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…In the study, citing the negative effects of financial stress on marital life, the participants stated that they were constantly arguing/fighting/tussling with their spouses, feeling restless and stressed out/pressured, and having thoughts of divorce/separation. Studies reported that economic, psychological, and social challenges faced during the pandemic as well as being in the same place and together all the time due to lockdowns, having fewer square meters per person in the house, not to mention children not having a room of their own, meant more domestic conflict, violence and divorce, and a decrease marital satisfaction (Alpar, 2020; Campbell, 2020; Pieh, O´Rourke, Budimir & Probst, 2020; Prime, Wade & Browne, 2020; Usher et al, 2020; Zhang & Ma, 2020). If conflicts between spouses cannot be managed, domestic violence, a decrease in marital satisfaction, and divorce are inevitable (Kaya & Akın, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, citing the negative effects of financial stress on marital life, the participants stated that they were constantly arguing/fighting/tussling with their spouses, feeling restless and stressed out/pressured, and having thoughts of divorce/separation. Studies reported that economic, psychological, and social challenges faced during the pandemic as well as being in the same place and together all the time due to lockdowns, having fewer square meters per person in the house, not to mention children not having a room of their own, meant more domestic conflict, violence and divorce, and a decrease marital satisfaction (Alpar, 2020; Campbell, 2020; Pieh, O´Rourke, Budimir & Probst, 2020; Prime, Wade & Browne, 2020; Usher et al, 2020; Zhang & Ma, 2020). If conflicts between spouses cannot be managed, domestic violence, a decrease in marital satisfaction, and divorce are inevitable (Kaya & Akın, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When the literature on the subject is examined, it is understood that the research significantly overlaps with what the company managers did during the pandemic days. According to the research findings of some researchers in Turkey, the necessity of employees to do their work in an electronic environment during pandemic days has made it necessary to benefit from digital innovation (Hidiroglu, 2020;Alpago, 2020). Thanks to digital innovation, employees have chosen to hold online meetings with multiple participants and see their service jobs from there.…”
Section: Discussionmentioning
confidence: 99%
“…This situation necessitates digital innovations based on information and communication technologies. The obligation of employees to do their work in an electronic environment during pandemic days necessitated digital innovation (Hıdıroglu, 2020;Alpago, 2020) Thanks to digital innovation, employees benefit from digital technologies to a great extent in holding online meetings with multiple participants in a virtual environment and especially performing service works. Digital innovation can only be possible with digital processes and technologies, the infrastructure being digital and appropriate, and the experience of digital experience.…”
Section: Digital Innovationmentioning
confidence: 99%
“…Araştırma sonucunda Covid-19 pandemisine karşı alınan önlemlerden olan sosyal izolasyon sürecinde kadına yönelik ve aile içi şiddettin arttığı, çalışan kadınların ev içi rollerinin arttığı, üniversite öğrenimini sürdürmekte olan genç kadınların ise evlerine döndükleri için eğitimlerine evde devam etmeleri ile ev içi rollerinin gündelik yaşamlarını zorlaştırmasına neden olduğu tespit edilmiştir. Alpar (2020), Covid-19 salgın sürecinde kadınların hane içindeki ücretsiz emeğini araştırmıştır. Araştırma nitel araştırma yöntemlerinden olan literatür taraması ile gerçekleştirmiştir.…”
Section: Türkiye'de Yapılan çAlışmalarunclassified